The Influence of Human Resource Management Dimensions on The Performance of Employees in The Regency Education and Culture Service North Konawe - Sahbin Barqi; Abd. Azis Muthalib; Muh. Nur (Maneggio, 2025)
The purpose of this study is to test and analyze the influence of: (1) the dimensions of human resource management on the performance of employees of the North Konawe Regency Education and Culture Office; (2) work tasks on the performance of employees of the North Konawe Regency Education and Culture Office; (3) quality on the performance of employees of the North Konawe Regency Education and Culture Office; (4) quantity on the performance of employees of the North Konawe Regency Education and Culture Office; (5) punctuality on the performance of employees of the North Konawe Regency Education and Culture Office; (6) cost effectiveness on the performance of employees of the North Konawe Regency Education and Culture Office.The design of this research is explanatory research.The population of this study is employeesDepartment of Education and Culture of North Konawe Regencyas many as 31 people and were also made respondents in this studyThe data analysis method used in this study is descriptive analysis and inferential statistics, namely SPSS. The results of the study stated that: (1) The dimensions of human resource management (work tasks, quality, quantity, timeliness and cost effectiveness) have a positive and significant effect on the performance of employees of the North Konawe Regency Education and Culture Office; (2) Work tasks have a positive and significant effect on the performance of employees of the North Konawe Regency Education and Culture Office; (3) Quality has a positive and significant effect on the performance of employees of the North Konawe Regency Education and Culture Office; (4) Quantity has a positive and significant effect on the performance of employees of the North Konawe Regency Education and Culture Office; (5) Punctuality has a positive and significant effect on the performance of employees of the North Konawe Regency Education and Culture Office; (6) Employee effectiveness has a positive but not significant effect on the performance of employees of the North Konawe Regency Education and Culture Office.